2014
DOI: 10.2147/ott.s54745
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of everolimus as salvage chemotherapy for ovarian clear cell carcinoma: a case report

Abstract: A case study using mammalian target of rapamycin complex 1 in recurrent ovarian clear cell carcinoma (CCC) was recently conducted. We report our experience with a patient suffering from recurrent ovarian CCC who achieved long-term disease control with everolimus administration. The patient was a 53-year-old woman who was diagnosed with recurrent ovarian CCC with dissemination throughout the abdominal cavity. Previously, she had received three chemotherapy regimens, but the disease was progressive and she showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In addition, Tinker, et al [84] found positive results after using temsirolius for a preliminary phase II study in patients with metastatic cervical cancer. The drugs were effective when administered together with paclitaxel/carboplatin for treating stage II/IV patients with clear cell adenocarcinoma on a clinical phase II trial [85].…”
Section: The Role Of Mtor Inhibitors In Cancermentioning
confidence: 99%
“…In addition, Tinker, et al [84] found positive results after using temsirolius for a preliminary phase II study in patients with metastatic cervical cancer. The drugs were effective when administered together with paclitaxel/carboplatin for treating stage II/IV patients with clear cell adenocarcinoma on a clinical phase II trial [85].…”
Section: The Role Of Mtor Inhibitors In Cancermentioning
confidence: 99%
“… Etanercept TNF Study of etanercept, a tumor necrosis factor-alpha inhibitor, in recurrent ovarian cancer [ 36 ]. Everolimus MTOR Effective use of everolimus as salvage chemotherapy for ovarian clear cell carcinoma: a case report [ 37 ]. Gefitinib EGFR Gefitinib (ZD1839) increases the efficacy of cisplatin in ovarian cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Everolimus MTOR Effective use of everolimus as salvage chemotherapy for ovarian clear cell carcinoma: a case report [37].…”
Section: Celecoxib Pdpk1mentioning
confidence: 99%
“…The grade 3/4 adverse events contained hyperglycemia in 15% of patients, stomatitis syndrome 7%, pain about 5% and asthenia 5%, most of which were mild and manageable [ 25 ]. Recently, everolimus has been investigated in varieties of recurrent/metastatic tumors, including recurrent ovarian clear cell carcinoma [ 26 ], relapsed or refractory chronic lymphocytic leukemia [ 27 ] and hepatocellular carcinoma [ 28 ], and brought new hope for cancer.…”
Section: Disscussionmentioning
confidence: 99%